The relationship between subconstructs of empathy and general cognitive ability in the context of policing - Inzunza, Miguel; Brown, Gavin T. L.; Stenlund, Tova; Wikström, Christina (Frontiers in Psychology, 2022)
Purpose – Empathy has been widely theorized as an important ability in professions such as policing, in which to perform well individuals require multiple and interacting abilities, not least when resolving conflict situations. Even so, there are few studies investigating how subconstructs of empathy relate to other constructs such as general cognitive ability. The purpose of this paper is to establish, after evaluating psychometric properties, relationships among measures of empathy and cognitive ability in a sample of Swedish police students (n = 157). Design/methodology/approach – Multiple latent variable models of how the different measures work to predict tasks that can be seen as proxies for the ability to understand another person’s situation and intentions are evaluated to determine the most robust relationship(s) within the data. Findings – We find support for the psychometric properties reported in previous studies with the used instruments. We also find support for perspective-taking, a cognitive empathy subconstruct predicting the ability to recognize emotions, and also the affective part of empathy, predicting general cognitive ability. These findings are discussed at length in the paper. Originality/value – This research adds more knowledge to the issue of how general cognitive ability relates to cognitive empathy and other subconstructs of empathy or Theory of Mind.